2023
DOI: 10.1097/coh.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Defining multimorbidity in people with HIV – what matters most?

Abstract: Purpose of reviewAlthough multimorbidity (defined as the coexistence of multiple conditions) presents significant health challenges to people with HIV, there is currently no consensus on how it should be defined among this population. This review aimed to examine the definition of multimorbidity in existing studies among people with HIV (n = 22).Recent findingsVariation in the definition of multimorbidity (in terms of the number and nature of conditions included) across studies among people with HIV was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Furthermore, as our measure of multi-morbidity is a count of the most common non-communicable diseases affecting PLWH, we may have underestimated its association with poorer multidimensional QoL. Had we adopted a broader definition, encompassing rarer comorbidities, the effect sizes may have been more pronounced 24 . This finding has major implications for HIV care in years to come as an estimated 28% of PLWH will have three or more non-communicable diseases in 2030, posing a threat not only their physical QoL but their psychological, social and environmental QoL as well 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as our measure of multi-morbidity is a count of the most common non-communicable diseases affecting PLWH, we may have underestimated its association with poorer multidimensional QoL. Had we adopted a broader definition, encompassing rarer comorbidities, the effect sizes may have been more pronounced 24 . This finding has major implications for HIV care in years to come as an estimated 28% of PLWH will have three or more non-communicable diseases in 2030, posing a threat not only their physical QoL but their psychological, social and environmental QoL as well 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of this study include the utilization of a broad spectrum of SDH in a well characterized cohort of people of African ancestry with HIV in South London, one of the most ethnically diverse and socioeconomically deprived areas in the UK. We were able to include mental health and chronic pain in our analyses, which are often excluded as conditions or risk factors [ 80 ] and included measures of HIV-related stigma and generalized discrimination as SDH.…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity is increasingly recognized in OPWH [4,25]. Indeed, these investigators has recently shown that multimorbidity is associated with frailty in this same cohort [26].…”
mentioning
confidence: 85%